KRISIS DAN NASIB BURUH DI PERDESAAN - Faturochman Faturochman (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
Farm and convection workers, who are part of the poor, have become even poorer during the economic crisis. Looking at their income in two different time periods, these groups have experienced an increase, but expenditure has instead been higher than income. Subjectively, these people indeed acknowledge that they have faced numerous problems during the crisis. Ironically, a number of them do not regard this as something that has increased their suffering. By some coincidence, there are employment opportunities in the study area that can potentially be used to survive. It is, however, difficult to predict how long this situation can sustain. They do not only suffer the consequence of sky rocketing prices of basic needs, which has eroded their purchasing power, but they also share the pain suffered by their employers. Their high dependence on the convection entrepreneurs, landowners and plantation entrepreneurs has made them very vulnerable to economic changes that take place like the current crisis.